1997
DOI: 10.1046/j.1365-3083.1997.d01-422.x
|View full text |Cite
|
Sign up to set email alerts
|

RT‐PCR Topography of Chronic Psoriasis Skin Based on Analysis of T‐Cell Receptor B Variable Region Gene Usage

Abstract: Psoriasis is a hyperproliferative inflammatory disease and 70% of patients develop a chronic plaque form. The pathogenesis of psoriasis is not known but evidence exists that T cells play a crucial role. The T cell V-gene receptor repertoire from psoriasis skin (different layers) was compared with peripheral blood T cells by employing RNA polymerase chain reaction (PCR) amplification. T cell receptor ( TCR) BV 5.1, 11, 12, 13.1 and 16 were utilized to a significantly higher degree in areas close to the basal la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Moreover, identical T cell clones have been detected in both skin and synovial lesions in patients with psoriatic arthritis (PsA) [31,32]. Notably, in the four studies where CD4 + and CD8 + T cells in the blood were analyzed separately, oligoclonality was detected among the CD8 + but not the CD4 + T cells [25,26,33,34].…”
Section: Reports On Oligoclonality Of Lesional T Cells In Psoriasismentioning
confidence: 99%
“…Moreover, identical T cell clones have been detected in both skin and synovial lesions in patients with psoriatic arthritis (PsA) [31,32]. Notably, in the four studies where CD4 + and CD8 + T cells in the blood were analyzed separately, oligoclonality was detected among the CD8 + but not the CD4 + T cells [25,26,33,34].…”
Section: Reports On Oligoclonality Of Lesional T Cells In Psoriasismentioning
confidence: 99%
“…This inconsistency has been reported by other authors, [20] and could be explained by the event referred to as the Koebner response [12]. Previous studies have reported selectivity of the clones displaying different TCR Vβ of infiltrated T-cells in psoriatic lesions: TCR Vβ-13 and -15 [11], TCR Vβ-5.1, -11, -12, -13.1 and -16 [21], TCR Vβ-3 and -13.1 [10], and more recently TCR Vβ-3, -13S2 and -21 [22]. This evidence is bound to studies of patient specimens with streptococcal infections.…”
Section: Discussionmentioning
confidence: 81%
“…There is other study indicating overexpression of this receptor in certain diseases, including the study of Ahangari et al [18] in which the expression of this receptor was increased in patients with asthma and breast cancer. In addition, in a study conducted by Saberi et al [20] overexpression of this receptor was indicated in lupus patients. In contrast, in a study in patients with schizophrenia and Tardive dyskinesia, it was found that the expression of this receptor in these diseases is reduced compared to healthy controls.…”
Section: -Ht 3 R a And Mao-a Mrna Quantitation By Real-time Pcrmentioning
confidence: 96%
“…Samples transferred to laboratory in flask. Peripheral blood mononuclear cells isolated from 4 ml of whole blood each sample based on the gradient density centrifugation technique via Ficoll-hypaque [20]. Then the cells in phosphate buffered saline (PBS) were washed and cell viability was determined by trypan blue staining and concentration of cells was normalized (Concentration 7 × 10 6 cells/ml).the percentage of viable cells was more than 99%.…”
Section: Pbmcs Isolation and Rna Extractionmentioning
confidence: 99%